Genetic spectrum and clinical features in a cohort of Chinese patients with isolated dystonia. Issue 4 (24th January 2023) - Li, Li‐Xi; Liu, Ying; Huang, Jie‐Hong; Yang, Yi; Pan, You‐Gui; Zhang, Xiao‐Long; Pan, Li‐Zhen; Jin, Ling‐Jing
Abstract: Dystonia is a genetically and phenotypically heterogeneous disorder that occurs in isolation (isolated dystonia) or in combination with other movement disorders. To determine the genetic spectrum in isolated dystonia, we enrolled 88 patients with isolated dystonia for whole‐exome sequencing (WES). Seventeen mutations, including nine novel ones, were identified in 19 of the 88 patients, providing a 21.59% positive molecular diagnostic rate. Eleven distinct genes were involved, of which TOR1A and THAP1 accounted for 47.37% (9/19) of the positive cases. A novel missense variant, p.S225R in TOR1A, was found in a patient with adolescence‐onset generalized dystonia. Cellular experiments revealed that p.S255R results in the abnormal aggregation of Torsin‐1A encoding by TOR1A . In addition, we reviewed the clinical and genetic features of the isolated dystonia patients carrying TOR1A, THAP1, ANO3, and GNAL mutations in the Chinese population. Our results expand the genetic spectrum and clinical profiles of patients with isolated dystonia and demonstrate WES as an effective strategy for the molecular diagnosis of isolated dystonia. Abstract : Seventeen mutations were identified in 19 of the 88 patients with isolated dystonia in the Chinese population, providing a 21.59% positive molecular diagnostic rate. Eleven distinct genes were involved, of which TOR1A and THAP1 accounted for 47.4% (9/19) of the positive cases.